Factors that help in the location of a distribution center: a bibliometric analysis - Bertolo, Rodolfo Santos; Freitas, Rodrigo Randow de (Brazilian Journal of Production Engineering, 2021)
Distribution Centers (DC) are fundamental facilities for the Supply Chain and are structured according to their demand and geographic location, in order to serve their buyers. When strategically located, a company's distribution centers provide a significant reduction in logistics costs. Thus, this study aims to map the scientific activity (bibliometrics) based on the theme: factors that help in the location of a CD, using in principle the entire coverage period of the main available databases: Web of Science - WOS, Scopus and Scielo. The process selected 11 relevant articles, aligned with the theme, a qualitative bibliometric analysis of the portfolio was carried out in order to characterize and analyze the articles. Most works have worked with Fuzzy theory and other methods of multicriteria analysis. And it can be seen that access, cost, environmental impact and resources are mentioned in several articles in the final analyzed portfolio.
Keywords: Distribution center; Logistics; Bibliometric; Location